Jump-to-Box exercise has an increasing effect on jumping ability in adolescents - H. Hendrik; Y. Ramba; . Arpandjam'an; G. Kapoor (National Electronic Information Consortium (NEICON), 2023)
Aim: To determine the most effective dose of the box jump exercise for increasing explosive leg muscle strength in adolescents, as measured by vertical jump height.Methods: This study is a field experimental study using a randomized control group pretest-posttest design by providing different doses of jump-to-box exercise. The experiment was conducted on Buqa'tum Mubarakah Junior High School students in Makassar, Indonesia, on February 16 to August 16, 2022 and obtained a total sample size of 60 male subjects aged 15-16 years. The participants were randomly divided into four experimental groups, each consisting of 15 people who were given jump-to-box exercises with different doses.Results: The results of the ANOVA test analysis showed that training with a loading dose of 24 cm and 5 minutes duration had a significant effect on increasing leg muscle explosive power with a p-value = 0.005. The other three groups did not show statistically significant improvements in jump height.Conclusion: The jump-to-box exercise with the box height of 24 cm and training duration of 5 minutes resulted in the highest average vertical jumping ability compared to other dose groups. This exercise protocol has an optimal effect on vertical jumping ability and limb explosive power in adolescents compared to other protocols.